The classical electromagnetic field. - Eyges, Leonard (Dover Publications, 1972)
In these notes we motivate the necessity for quantizing the electromagnetic field, we outlinea procedure for doing that, and then we carry out the classical part of that procedure, which is to find a classical Hamiltonian for the combined system of matter plus electromagnetic field. In a subsequent set of notes we shall quantize this classical Hamiltonian and study the results. Standard references for the material in these notes include Heitler, The Quantum Theory of Radiation and Cohen-Tannoudji, Dupont-Roc and Grynberg, Photons and Atoms.